2020
DOI: 10.3389/fbioe.2020.01030
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoke and Inhaled Drugs Alter Expression and Activity of Multidrug Resistance-Associated Protein-1 (MRP1) in Human Distal Lung Epithelial Cells in vitro

Abstract: Multidrug resistance-associated protein-1 (MRP1/ABCC1) is highly expressed in human lung tissues. Recent studies suggest that it significantly affects the pulmonary disposition of its substrates, both after pulmonary and systemic administration. To better understand the molecular mechanisms involved, we studied the expression, subcellular localization and activity of MRP1 in freshly isolated human alveolar epithelial type 2 (AT2) and type 1-like (AT1-like) cells in primary culture, and in the NCI-H441 cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Of note, the Nrf2 agonists sulforaphane and compound 7 were both found to reverse defects in opsonic phagocytosis of Streptococcus pneumoniae and nontypeable Hemophilus influenzae by COPD alveolar macrophages (AMs) (32). Furthermore, sulforaphane was also reported to reverse the negative effect of CS extract on MRP1 activity (33). The latter finding enhances our computational predictions regarding the contribution of the Drosophila ABC transporters in the induction of COPDrelated phenotypes.…”
Section: Discussionsupporting
confidence: 66%
“…Of note, the Nrf2 agonists sulforaphane and compound 7 were both found to reverse defects in opsonic phagocytosis of Streptococcus pneumoniae and nontypeable Hemophilus influenzae by COPD alveolar macrophages (AMs) (32). Furthermore, sulforaphane was also reported to reverse the negative effect of CS extract on MRP1 activity (33). The latter finding enhances our computational predictions regarding the contribution of the Drosophila ABC transporters in the induction of COPDrelated phenotypes.…”
Section: Discussionsupporting
confidence: 66%
“…Though the expression of PEPT2 mRNA was decreased by corticosteroid treatment, no apparent change in PEPT2 protein expression was observed under the present treatment conditions, as confirmed by Western blotting and by CLSM after immunostaining. Recently, Selo et al 26) examined the effect of inhaled compounds, including BUD and cigarette smoke extract (CSE), on multidrug resistance-associated protein-1 (MRP1; an efflux transporter) using human alveolar type II and type Ilike epithelial cells in primary culture and H441 cells. In that study, they first compared the mRNA and protein expression of MRP1 in type II and type I-like epithelial cells and found that MRP1 protein expression was significantly higher in type I-like cells than in type II cells, while the mRNA expression level was similar between these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinomic alveolar A549 and NCI-H441 cell lines have commonly been used as a model for alveolar epithelium in different studies and seem to have a good ability to model lung injury and repair [22][23][24][25]. Furthermore, bronchial epithelial cell lines such as BEAS-2B are usually co-cultured with the epithelial cell line A549 to model airway epithelial cell injury in a cigarette smoke model [26], allergic airway inflammation [27], acute respiratory distress syndrome [28] and lung cancer [29].…”
Section: Lung Cell Culturementioning
confidence: 99%